Retromandibular vien as a land mark to locate marginal mandibular branch of cranial nerve VII during parotid salivary gland surgery - Basim Ali Qasim; Mohammed Rhael Ali; Azhar abed oudah (International Journal of Medical Toxicology and Legal Medicine, 2025)
Background: Parotid gland surgery is a closed surgery due to the delicate nature of this area particularly the facial nerve (CN VII) marginal mandibular branch. Sparing this nerve from injury is important to avoid such risks as facial paralysis and similar severe, permanent loss of function. The retromandibular vein is generally utilized as one of the anatomical landmarks used to ascertain the location of marginal mandibular branch of cranial nerve VII during parotidectomy so as to avoid the damage of the nerve. Methodology: A case control study was carried out on 50 patients with parotid gland tumours, aged between 13 and 70 years. All patients’ operation was a standardized parotidectomy, and for the marginal mandibular branch of the facial nerve identification, the retromandibular vein was employed. Cohort information obtained includes demographic characteristics, laterality of the tumour, benign or malignant status of the tumour, and facial nerve function status post surgery. Descriptive statistics of the study variables and two Groups t-tests and analyses of variance (ANOVAs) were used to determine the between group differences Participants’ and researchers’ demographic information was also checked for difference using chi-square and p value was used to compare the differences with a significance level of 0.05. Results: Among the 50 patients, 86 % had tumor right side with a suggestion of tumor laterality (p = 0.021). Malignant tumors accounted for only 2% cases, and most of this (96%) were located in the parotid gland; the commonest histological type was pleomorphic adenoma. Overall, facial nerve preservation was most successful in benign tumor patients and 81.6% were classified as being without postoperative alterations on the facial nerve (Grade I). The worst outcome was noted in the single malignant case, which had Grade IV nerve injury. Another aspect concerning nerves was made, where tumor size has been revealed us as the factor impacting the nerves with larger size of the tumor the mean size of which was 4.5 cm had worse result at nerves (p=0.008). Conclusion: This paper provides a clear chronological description of the anatomic landmark encountered during the identification of the marginal mandibular branch of cranial nerve VII during parotid gland surgery using the retromandibular vein. In this landmark significantly decreases the risk of facial nerve injury when it is used. Our results put emphasis on recognizing the disease during early stage and accurate surgical procedure, especially for big and malignant tumour, to improve patients’ prognosis. The need for further investigation into the facts that provoked tumor laterality, as well as a more precise approach to the parotidectomy procedure, was also discussed.